MAKNA KALIMAT UMPATAN DALAM BAHASA MELAYU TERNATE DI MEDIA SOSIAL - Fida Febriningsih (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
Language is closely related to the norms and customs of its speakers. Language reflects the character, expression, and culture of the speaker, both oral and written. Social media as one of the means to express feelings through words or sentences, in its development, makes some users forget politeness in language. Comments and uploads on social media often contain swearing or swearing. This does not only happen in Indonesia but also the use of language in the use of local languages, including Malay Ternate (BMT) a language of inter-ethnic in North Maluku. This study aims to describe the lexical and pragmatic meanings of BMT speech that contain swearing.The results show that the form of swearing in BMT sentences on social media uses animal names such as anjing and babi, curses with bodysuch as trada otak, and negative professions such as lonte, bangsat, janda longgar, and janda ayam-ayam, curses in the form of phrases such as bendahara dgn ijazah SMA sj, curses of adjectives such as sombong, biadab, makan puji, and kurang ajar, curses of verbs such as cukimai, curses in the form of sentences such as ngn itam baru anjing itu putih, curses that describe the state of a person like ngn itam, and curses using plant names like kalapa kao. The remarks in the BMT mean expressing feelings of anger, annoyance, disappointment, and humiliation.